2010
DOI: 10.1080/13669870903139070
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐level analysis of major trends in environmental health risk governance

Abstract: Internationally but also within countries, large differences exist regarding how environmental health risks (EHRs) are governed. Despite these differences, at a meta-level some general trends can be discerned that may point to a convergence of EHR governance regimes. One, EHR governance regimes are increasingly taking into account cost-benefit considerations, sectoral goals outside the health risk domain, public concerns and stakeholder interests in early stages of decisionmaking. Two, EHR objectives are incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition, norm setting was driven by an equal protection for all rationales, implying uniform goals (Runhaar et al, 2010). In addition, norm setting was driven by an equal protection for all rationales, implying uniform goals (Runhaar et al, 2010).…”
Section: Urban Environmental Governance Around 1990mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, norm setting was driven by an equal protection for all rationales, implying uniform goals (Runhaar et al, 2010). In addition, norm setting was driven by an equal protection for all rationales, implying uniform goals (Runhaar et al, 2010).…”
Section: Urban Environmental Governance Around 1990mentioning
confidence: 99%
“…Municipalities were mainly in charge of policy implementation and responsible for meeting predefined objectives. Hence, the predominant policy level at which key actors operated was the state level (Runhaar et al, 2010). The position of other stakeholders was determined by the central government, although industry and other stakeholders were actively lobbying.…”
Section: Urban Environmental Governance Around 1990mentioning
confidence: 99%
See 1 more Smart Citation
“…For a general critique of the reductionist approach of U.S. environmental regulation, see Heinzerling (). In a study of 10 countries, Runhaar, Driessen, Van Bree, and Van der Sluijs () found a partial and not fully consolidated trend in environmental health regimes from specialized regimes to more differentiated and integrated regimes. Collier and Lazer () examine the way that population‐level thinking and the recognition of the interconnectedness of systems led to the idea of “vital systems security” in civil defense planning, which eventually spread to other domains, such as pandemic planning and natural disaster planning.…”
mentioning
confidence: 99%
“…Second, the approach examines the content as well as the organizational structure, which both influence institutional stability or change. An alternative analytical framework would have been the framework developed by Runhaar et al [36,37] for characterizing, explaining, and evaluating environmental health risk governance regimes. The latter emphasizes the judicial approach, primarily focusing on the rules of the game and on procedures.…”
Section: Discussionmentioning
confidence: 99%